2005
DOI: 10.1002/ar.b.20061
|View full text |Cite
|
Sign up to set email alerts
|

Feulgen reaction study of novel threadlike structures (Bonghan ducts) on the surfaces of mammalian organs

Abstract: Threadlike structures on the surfaces of internal organs, which are thought to be part of the Bonghan duct system, were first reported about 40 years ago, but have been largely ignored since then. Recently, they were rediscovered, and in this study we discuss the Feulgen reaction that specifically stains DNA in order to identify these structures on the surface of rabbit livers as part of the Bonghan system. The distribution, shapes, and sizes of their nuclei are found to be similar to those of intravascular th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 12 publications
9
87
0
Order By: Relevance
“…The morphological characteristics of Figs 6 and 7 are identical to those of the primomicrocells that have been reported in previous works (Shin et al 2005;Ogay et al 2006;Kwon et al 2007;Baik et al 2009). These primo-microcells have been thought to play a role in cell development, tissue renewal, and wound healing (Kim 1965;Fujiwara 1967).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The morphological characteristics of Figs 6 and 7 are identical to those of the primomicrocells that have been reported in previous works (Shin et al 2005;Ogay et al 2006;Kwon et al 2007;Baik et al 2009). These primo-microcells have been thought to play a role in cell development, tissue renewal, and wound healing (Kim 1965;Fujiwara 1967).…”
Section: Discussionsupporting
confidence: 84%
“…Very recently, some morphological features of primomicrocells have been studied (Ogay et al 2006;Kwon et al 2007;Baik et al 2009), providing evidence for the circulatory function of the primo-vessels (Shin et al 2005;Lee et al 2007;Sung et al 2008Sung et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…A distinction based on gross anatomical features (Shin et al, 2005) and histological details ) in rabbits was reported before. The primo vessels floating inside the flow of lymph vessels of rats and rabbits manifestly demonstrated that they are two different systems (Lee et al, 2006;Johng et al, 2007;Lee and Soh, 2008).…”
Section: Discussionmentioning
confidence: 82%
“…The presence of the PVS was observed on the surfaces of internal organs like the liver, stomach, large intestine and bladder [4] .This subset of the PVS is called the organsurface PVS (OS-PVS). Another major subset, which has been observed, is the PVS floating in the flow of blood [5] and lymph [6] or in the cerebrospinal fluid of the brain and the spinal cord [7] .…”
Section: Reviewmentioning
confidence: 99%